Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Prove that: (a=alpha)Tan a +2tan 2a+ 2^2tan2^2a +....................... 2^n-1tan2^n-1a + 2^ncot2^n a = cot a

Prove that: (a=alpha)Tan a +2tan 2a+ 2^2tan2^2a +....................... 2^n-1tan2^n-1a + 2^ncot2^n a = cot a

Grade:12th pass

1 Answers

Akash Ojha
20 Points
4 years ago
We know, cotA - tanA = 2cot2A=> tanA = cotA - 2cot2AHence, the above series can be rewritten as:-(cotA - 2cot2A) + 2(cot2A - 2cot4A) + 2^2(cot4A - 2cot8A) + ........+ 2^n-1(cot2^n-1A - 2cot2^nA) + 2^ncot2^nA= cotA(Since all the rest terms cancel each other out except first term cotA)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free